PB4. In vivo analysis of hippocampal vascularization patterns in patients with cerebral amyloid angiopathy – A 7T time-of-flight MR-angiography study. Issue 8 (August 2018) - Perosa, V.; Priester, A.; Neumann, K.; Spallazzi, M.; Düzel, E.; Schreiber, S.
Abstract : Background: Hippocampal integrity is crucial for many cognitive functions (e.g. episodic memory) commonly affected in Alzheimer's dementia (AD). The hippocampus compared to several cortical areas seems to be less able to cope with oxidative stress as a result of e.g. hypoperfusion and anoxia (Duvernoy et al., 2005), which may rely on different hippocampal vascularization patterns based on the hippocampal arteries' origin from the posterior cerebral artery (PCA) or from both, PCA and anterior choroidal artery (AChA) (Marinkovic et al., 1992; Spallazzi et al., under review). There is considerable overlap between AD pathology and sporadic cerebral amyloid angiopathy (CAA), that is vascular ß-amyloid deposition found throughout the whole brain also affecting the hippocampal arteries and leading to cognitive decline through several downstream pathologies comprising e.g. hypoperfusion, microbleeds or microinfarcts. Methods: We performed high-resolution 7 Tesla (T) and 3 T magnetic resonance imaging (MRI) comprising time-of-flight (ToF) magnetic resonance angiography (MRA) (7 T) on so far 12 non-demented patients diagnosed to suffer from CAA according to Boston criteria (mean [SD] age 70.9 [6.40] years, 66.67% male) and 20 age-matched healthy controls (70.38 [4.868] years, 45% male). MRI was considered as a baseline. Furthermore, regional blood perfusion was measured using Arterial Spin Labelling (ASL) at 3 T MRI (Grade et al., 2015) and will be correlated to the vascularization patterns. Cognitive function was assessed at baseline and will be measured during at least two follow-ups to extract various composite scores adjusted for education. Conversion to dementia will be diagnosed according to standardized criteria. A hippocampal mask was created using FreeSurfer (Fischl et al., 1999) and adopted as an anatomical landmark to analyze 7T ToF MRA data. Hippocampal vessels as well as the different distribution patterns of the right and left hemispheres will be visually inspected and vascularization patterns will be classified using MeVisLab (https://www.mevislab.de ). Hypothesis: Based on the proposed hippocampal vascularization patterns we here hypothesize to find different CAA phenotypes characterized by two features, (i) the extent of CAA-related downstream pathologies, and (ii) the resilience against those downstream pathologies resulting in different slopes of cognitive decline as well as various dementia conversion rates. Thereby, higher hippocampal perfusion and less microbleeds or microinfarcts are expected to be found in hemispheres where PCA and AChA are both participating to hippocampal vascularisation. CAA patients displaying that hippocampal vascularization pattern are further hypothesized to reveal higher cognitive reserve mechanisms resulting in slower cognitive decline and lower dementia conversion rates.